Can Sonography Be Used to Estimate Deep Abdominal Muscle Activation in Different Static Arm Positions While Standing?. (3rd December 2016) - Eriksson Crommert, Martin; Unsgaard‐Tøndel, Monica; Vasseljen, Ottar
Abstract : Objectives: The aim of this study was to investigate whether sonography is a reliable tool for measuring deep abdominal muscle activation in different static arm positions while standing. Methods: Sonographic recordings were made of the transversus abdominis and obliquus internus abdominis in 4 different static arm positions that varied with regard to the postural demand and loading direction posed on the trunk. Ten nonconsecutive repetitions of each arm position were performed, and thickness measurements were made at 2 locations within each muscle. Reliability was analyzed by the generalizability theory; comparisons regarding thickness measurements were made by repeated‐measures analyses of variance; and fascial sliding was analyzed by a 1‐sample t test. Results: Averaged over all repetitions, arm positions, and the 2 measurement locations, the thickness measurements were highly reliable for both the obliquus internus abdominis and transversus abdominis. The transversus abdominis was thicker with shoulders flexed than with shoulders extended or arms above the head ( P < .021) and with arms alongside the body compared with shoulders extended ( P < .005). There was no thickness difference between arm positions for the obliquus internus abdominis ( P = .059). Conclusions: The results indicate that sonographic recordings of the obliquus internus abdominis and transversus abdominis in different static arm positions while standing provide reliable measurements of muscle thickness. However, in light of previously reported electromyographic data, the results raise some concerns regarding the validity of using thickness measurements as proxies for muscle activation in positions that may induce passive muscle deformation.